2012
DOI: 10.1155/2012/676073
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy in Celiac Disease

Abstract: Capsule endoscopy (CE) has been increasingly used for diagnosing disease of the small bowel. It is an attractive technique for assessing celiac disease (CD) because it is noninvasive and provides a close and magnified view of the mucosa of the entire small bowel. The aim of this paper is to update the current data on the use of CE for diagnosing villous atrophy and complications of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The so-called endoscopic markers of celiac disease include shortening and thickening of intestinal villi, or a lack of intestinal villi (fissures); flattening or a lack of circular folds; fissures of the mucosa, a mosaic mucosal pattern or granulation of the mucosa [12,15]. The positive predictive value of endoscopic markers of celiac disease has been assessed at 68%; more specifically, a mosaic structure of the duodenal mucosa has been assessed at 65%, granulation of mucosa at 75.5% and scalloping of circular folds at 64.4% [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called endoscopic markers of celiac disease include shortening and thickening of intestinal villi, or a lack of intestinal villi (fissures); flattening or a lack of circular folds; fissures of the mucosa, a mosaic mucosal pattern or granulation of the mucosa [12,15]. The positive predictive value of endoscopic markers of celiac disease has been assessed at 68%; more specifically, a mosaic structure of the duodenal mucosa has been assessed at 65%, granulation of mucosa at 75.5% and scalloping of circular folds at 64.4% [16].…”
mentioning
confidence: 99%
“…The positive predictive value of endoscopic markers of celiac disease has been assessed at 68%; more specifically, a mosaic structure of the duodenal mucosa has been assessed at 65%, granulation of mucosa at 75.5% and scalloping of circular folds at 64.4% [16]. According to various data, those markers are present in 67-93% patients with celiac disease [15].…”
mentioning
confidence: 99%
“…In the study performed by Akram et al ,10 7 patients of 15 were examined with capsule endoscopy, and showed villous pathology restricted to the proximal small bowel in all patients but one, while we found shortened villi throughout the small bowel. WCE is a valuable diagnostic tool in a variety of diseases where mucosal damage is involved, such as coeliac disease and refractory coeliac disease 12. However, in coeliac disease, capsule endoscopy does not contribute to diagnosis when compared with duodenal biopsies 13.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, none of the previous reports have included carriers of HLA-DQ2 or DQ8 or patients who developed villous atrophy in the small intestine before EATL occurrence in the Japanese populations. Data in Japan is scarce regarding the significance of capsule endoscopy (CE) and magnifying narrow-band imaging (NBI) in the management of EATL in patients with CeD, although there are a couple of publications on these in the Western countries [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%